1995
DOI: 10.1021/jm00013a011
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal Affinity Labels of the Estrogen Receptor. 2. 17.alpha.-[(Haloacetamido)alkyl]estradiols

Abstract: In a previous study, we described affinity labeling of the lamb uterine estrogen receptor by 17 alpha-[(bromoacetoxy)alkyl/alkynyl]estradiols. However, the intrinsic receptor-alkylating activities of these compounds were probably very hampered by their poor hydrolytic stability in estrogen receptor-containing tissue extracts. Therefore, (i) to develop affinity labels of the receptor not susceptible to hydrolysis and (ii) to specify the structural requirements for 17 alpha-electrophilic estradiol derivatives to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…6. Ion identification was facilitated by comparison of the obtained spectrum with that of the homologous species involving the 14 (i) all detected ions involving an alkylated portion of CysLys included the Cys S and various portions of Cys or CysLys; (ii) no signal was found that would correspond to an alkylated portion of Lys; (iii) signals characterizing unsubstituted Lys (immonium, X and Y ions) were present, whereas no signal was found at m/z values which would correspond to unsubstituted Cys fragments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6. Ion identification was facilitated by comparison of the obtained spectrum with that of the homologous species involving the 14 (i) all detected ions involving an alkylated portion of CysLys included the Cys S and various portions of Cys or CysLys; (ii) no signal was found that would correspond to an alkylated portion of Lys; (iii) signals characterizing unsubstituted Lys (immonium, X and Y ions) were present, whereas no signal was found at m/z values which would correspond to unsubstituted Cys fragments.…”
Section: Resultsmentioning
confidence: 99%
“…14 C-labeled or non-radioactive electrophile (two-fold concentration relative to the amount of GST-LBD, ∼2-3 nmole) was added to glutathione-sepharose-bound GST-LBD in 0.5 mL of ice-cooled phosphate-buffered saline (pH 8.0), containing 5% dimethylformamide. The mixture was rotated for 30 min at 2 • C and then the matrix was drained, and washed with phosphate-buffered saline to eliminate unreacted electrophile.…”
Section: Gst-lbd Binding Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by recent reports [12,15,19,20], which indicated that it is difficult to account for the estrogenic/antiestrogenic activity of an ER ligand on the basis of the orientation of helix 12 in crystallized ER LBD-ligand complexes. To enhance the overall understanding of the molecular action of estrogens and antiestrogens, we sought to directly identify, within ER␣ LBD, the covalent attachment sites of estrogenic estradiol (E 2 ) 17␣-derivatives [21] and antiestrogenic E 2 11␤-derivatives [22] through mass spectrometry (MS) analysis and then to interpret the biochemical data by molecular modeling.…”
Section: Introductionmentioning
confidence: 99%
“…1), one previously tested ER␣ affinity label [21], directly derives from 17BAPE 2 by removal of the (CH 2 ) 2 module from the 17␣-(CH 2 ) 3 group. In 17BAME 2 the maximal distance between the steroidal C-17 and the electrophilic carbon (-carbon) is ∼35% lower than that of the homologous distance in 17BAPE 2 and the degree of freedom of the -carbon is two instead of four.…”
Section: Introductionmentioning
confidence: 99%